Environmentally Friendly Approaches Assisted Machining of Aluminum Alloy 7075-T6 for Automotive Applications: A Review - Yazid, MZA; Zainol, Azreen (International Journal of Integrated Engineering, 2019)
Nowadays, aluminum alloy 7075-T6 has received a high demand in the automotive industry due to its advantages in the aerospace industry, which possessing exceptional mechanical combinations and chemical elements such as high tensile strength, high strength, high corrosion resistance, zinc, magnesium, and copper to increase their strength. Nevertheless, environmentally friendly approaches are necessary to improvise surface quality and machining performances as well as minimize the adverse environment. This has directly influenced the trend of approach or strategy of cutting fluids towards the machining of high-performance material in the automotive industry. There have been some probations to decrease the volume of cutting fluid application in machining. The approach of cutting fluids become prominent indicator in contribution to minimize the application of cutting fluid so that the machining of aluminum alloy 7075-T6 become more effective and environmental friendly. Thus, results can be found in the low tool wear, minimum heat energy generated and reduced machining cost in encouraging the application of MQL as viable formulations to enhance the machining performance and machined surface quality. The primary objective of review work is summarized all the emerging environmentally friendly approaches towards the high-performance material. Impact of machining process parameters on dependent variables such as surface integrity, tool wear, chip formation, and mechanical properties have been discussed in the light of the findings of the recent study.